Treffen sich Akteur und Zuschauer? Zur Rolle des Richters in Hannah Arendts Urteilstheorie - Rosenmüller, Stefanie (HannahArendt.net, 2005)
This PhD thesis pursues two lines of inquiry. It attempts to interpret Arendt as a "third position” within the debate between legal positivism and modern natural law, one which legitimates and delimits juridical forays into the extra-law sphere of the pol